The Balkan Reconquista and Turkey's Forgotten Refugee Crisis - Holt, William H., 1979- (Book collections on Project MUSE., 2019)
"The Balkan reconquista and Turkey's forgotten refugee crisis brings together a wide array of eyewitness accounts to provide unprecedented detail on the plight of Muslims during the Russo-Ottoman war of 1877-78 when massacres, rapes, and the looting and burning of their villages led hundreds of thousands of Muslims to flee from Bulgaria into Turkey. The book explores the tensions between Muslims and Christians in the Balkans before 1877, the ethnic cleansing and migration that resulted, the subsequent refugee crisis in Istanbul, and the resettlement of refugees in Anatolia. Author William Holt seeks to understand why these events, clearly important in Turkish history, are so little known in Turkey today. In crisp and engaging prose, he provides a compelling narrative and insightful analysis about human suffering and social memory"--Provided by publisher.